Factors that influenced component localization: a study in Honda Malaysia Sdn Bhd (HMSB) / Hamidah Rosli - Rosli, Hamidah (Faculty of Business and Management, 2011)
The Multinational Corporation (MNCs) are faced with the choice of localising supplies when they establish manufacturing subsidiaries overseas. These organizational approaches for localization within large companies are many and varied. Localization activity presents significant opportunities to the firm’s for improving profits margins and reducing cost. Thus, the localization of component sourcing is a key concern to manufacturing subsidiaries in achieving successful performance.